Speech Acts in the Discourse of Prophet Joseph Peace be Upon Him in the Holy Quran: A Deliberative Approach - Nazzal, Nibal Nabeel (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aims to present a deliberative reading within the framework of the speech act theory to unveil the deliberative tendencies in the discourse of Joseph Peace be upon him as a boy, a youth, an accused man, a prisoner, a ruler, a son, a brother, etc. Furthermore, this study uncovers key stages in Joseph’s life and examines speech acts in various contexts to achieve specific communicative goals. Methods: This research is descriptive and analytical; and conducted a deliberative reading of the discourse of Joseph Peace within the framework of the speech act theory. In addition, this research is twofold: A preliminary theoretical study which relies on the nature of speech acts, their types and meanings; and a practical demonstration of the speech acts in the discourse of Joseph. Results: According to the deliberative reading of the Holy Quranic discourse within the framework of the speech act theory, it comes to light that the discourse of Joseph peace be upon him in the Quran has more than one type, and carries more than one meaning. Such multiple meanings rely on the communicative context of this discourse as well as on its purpose and influences to ensure the continuity of the communicative process. Conclusions: This study recommends further studies pertaining to the discourse of the Quran within the framework of the deliberative speech act theory since this theory has changed the traditional view of speech by focusing on the various factors and elements of discourse.